2014
DOI: 10.1038/ncomms6554
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-enhanced gating effect at the LaAlO3/SrTiO3 interface

Abstract: Electrostatic gating field and light illumination are two widely used stimuli for semiconductor devices. Via capacitive effect, a gate field modifies the carrier density of the devices, while illumination generates extra carriers by exciting trapped electrons. Here we report an unusual illumination-enhanced gating effect in a two-dimensional electron gas at the LaAlO 3 /SrTiO 3 interface, which has been the focus of emergent phenomena exploration. We find that light illumination decreases, rather than increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 29 publications
(45 reference statements)
4
64
0
1
Order By: Relevance
“…Furthermore, we have also recently being able to control the carrier density by shining light using the photoconductivity effect in addition to the back-gate [30]. We found that light illumination decreases, rather than increases, the carrier density of the gas when the interface is negatively gated through the STO layer, and the density drop can be 20 times as large as that caused by the conventional capacitive effect.…”
Section: Modulation-dopingmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we have also recently being able to control the carrier density by shining light using the photoconductivity effect in addition to the back-gate [30]. We found that light illumination decreases, rather than increases, the carrier density of the gas when the interface is negatively gated through the STO layer, and the density drop can be 20 times as large as that caused by the conventional capacitive effect.…”
Section: Modulation-dopingmentioning
confidence: 90%
“…Owing to the greater sensitivity of their electronic properties and because of the wider range of phenomena that can be observed in these interfaces, the implications for basic physics and technological application using oxide heterostructures are likely to be enormous. [27], field-induced metal-insulator transition [29], and optical sensitivity [30]. The mechanism underlying the two-dimensional electron gas (2DEG) at the interface between two insulating oxides of LAO and STO is still unclear and under a debate.…”
mentioning
confidence: 99%
“…7 Therefore the 2DEG of STO interfaces exhibits a large number of interesting properties, such as 2D superconductivity 8,9 , magnetism 10 , and metal-insulator transitions 11,12 . However, the relatively low electron mobility (~1000 cm 2 V -1 s -1 at 2 K) and the high sheet carrier concentration (10 13 -10 14 cm -2 ) of typical STO 2DEGs have hindered the applications such as demonstration of quantum Hall effects [13][14][15] or the achievement of sizable field effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, STO is also a model system for mixed ionic and electronic conductors at high temperatures, due to the presence of unintentional dopants (typically Fe, Al, and Mn) which act as acceptor type impurities [3]. In recent years, STO has attracted increasing attention for application in oxide electronics as active materials, particularly upon the discovery of a two-dimensional electron gas (2DEG) at the STO surface [4] or its interface with another band insulator, such as perovskite LaAlO3 (LAO) [5] or spinel γ-Al2O3 (GAO) [6].The 2DEG of STO interface to another oxide insulator has drawn extensive attention because of the emergent properties which are not observed in the bulk counterparts, such as 2D superconductivity [7,8], magnetism [9], quantum Hall effect [10], as well as light enhanced field effects [11]. On the…”
mentioning
confidence: 99%
“…The 2DEG of STO interface to another oxide insulator has drawn extensive attention because of the emergent properties which are not observed in the bulk counterparts, such as 2D superconductivity [7,8], magnetism [9], quantum Hall effect [10], as well as light enhanced field effects [11]. On the…”
mentioning
confidence: 99%